2014
DOI: 10.1074/mcp.o113.035915
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Utility of Mass Spectral Binning in Proteomic Experiments by SPectral Immonium Ion Detection (SPIID)

Abstract: Unambiguous identification of tandem mass spectra is a cornerstone in mass-spectrometry-based proteomics. As the study of post-translational modifications (PTMs) by means of shotgun proteomics progresses in depth and coverage, the ability to correctly identify PTM-bearing peptides is essential, increasing the demand for advanced data interpretation. Several PTMs are known to generate unique fragment ions during tandem mass spectrometry, the so-called diagnostic ions, which unequivocally identify a given mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…5 ). Formylation specifically forms immonium ion at m/z 112 compared with di-methylation, as reported in a previous study [32] , [33] . Formylation of immonium ion at m/z 112.076 was also observed in our results ( Fig.…”
Section: Resultssupporting
confidence: 62%
“…5 ). Formylation specifically forms immonium ion at m/z 112 compared with di-methylation, as reported in a previous study [32] , [33] . Formylation of immonium ion at m/z 112.076 was also observed in our results ( Fig.…”
Section: Resultssupporting
confidence: 62%
“…presented a tool for spectral binning to identify masses exclusive for a given PTM compared to unmodified peptides (37). Following up on and extending this idea, we implemented an intensity weighted m/z aggregation strategy for fragment ions originating from thousands of spectra and for all the 21 modifications and fragmentation modes used in our study.…”
Section: Downloaded Frommentioning
confidence: 99%
“…It was recently reported that Hme-bearing peptides can give rise to a specific immonium ion in tandem mass spectra upon fragmentation ( 12 ). The Hme immonium ion has a mass of 124.087 atomic mass units, a region with low background signal in mass spectra ( 92 ). Inspection of mass spectra for this immonium ion can corroborate Hme events and enable Hme bearing peptides to be distinguished from those with SNPs or other monomethylation events.…”
Section: Challenges In Analyzing Hmementioning
confidence: 99%